Restrained nonsplit-[1, 2] domination number of graphs-I. (December 2018) - Mahadevan, G; Bhagavathi Ammal, V G; Renuka, K
Abstract: A restrained dominating set S ⊆ V ( G ) in a graph G is said to be restrained nonsplit-[1, 2] dominating set, if for every vertex υ ∈ V − S, 1 ≤ | N (υ) ∩ S | ≤ 2 and < V − S > is connected. The minimum cardinality of restrained nonsplit-[1, 2] dominating set ( rns [1, 2]- set ) is called restrained nonsplit-[1, 2] domination number and is denoted by γ rns [1, 2] ( G ). In this article, we launch the new concept called restrained nonsplit-[1, 2] domination number of graphs.